1996
DOI: 10.1152/ajpgi.1996.271.6.g993
|View full text |Cite
|
Sign up to set email alerts
|

HIP/PAP is an adhesive protein expressed in hepatocarcinoma, normal Paneth, and pancreatic cells

Abstract: Human hepatocarcinoma-intestine-pancreas (HIP) cDNA, isolated from a hepatocellular carcinoma, encodes a C-type lectin. According to published cDNA sequences, HIP protein is identical to human pancreatitis-associated protein (PAP). In these sequences, a putative signal peptide and the carbohydrate recognition domain (CRD) can be recognized. In the present study, we established transgenic mice to drive the production of soluble recombinant HIP/PAP protein in the milk of lactating animals; using this model, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 0 publications
9
118
1
Order By: Relevance
“…The cloning of HIP/PAP cDNA into an expression vector containing the His-tag has been described elsewhere (24). The recombinant protein contained a 6 Histidine tag at the NH 2 -terminal, followed by the putative signal sequence, the putative propeptide, and the COOH-terminal carbohydrate recognition domain (CRD) of HIP/PAP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloning of HIP/PAP cDNA into an expression vector containing the His-tag has been described elsewhere (24). The recombinant protein contained a 6 Histidine tag at the NH 2 -terminal, followed by the putative signal sequence, the putative propeptide, and the COOH-terminal carbohydrate recognition domain (CRD) of HIP/PAP.…”
Section: Methodsmentioning
confidence: 99%
“…Pancreatic Reg expression in NOD mice was studied with two different affinity-purified rabbit-derived polyclonal anti-Reg primary antibodies. One was produced against a fusion protein of the CRD of HIP/PAP (HIP-CRD) with glutathion-S-transferase (24), and the other was produced against recombinant rat PAP1, the homologue to mouse RegIII␤. Guinea pig anti-insulin antibodies, HRP-labeled anti-guinea pig antibodies, and HRP-labeled anti-rabbit antibodies were purchased (Zymed, Sigma).…”
Section: Purification Of Cd8mentioning
confidence: 99%
“…20 We discovered the human HIP/PAP gene by differential screening of a hepatocarcinoma 15 and demonstrated that HIP/PAP promoted hepatocyte adhesion in primary cultures and interacted with the proteins of the extracellular matrix. 21 Rat PAPI also promoted the growth of epithelial intestinal cells. 22 In neurons, rat Reg2/HIP/PAPI prevented cell death in primary motor neuron cultures 23 and stimulated mitogenesis in Schwann cells and nerve regeneration.…”
mentioning
confidence: 91%
“…Regenerating islet-derived (Reg) gene family, initially discovered in connection with islet regeneration after experimental injury to rat pancreas, encodes for a small group of proteins involved in the control of epithelial cell proliferation and differentiation in various organs, including pancreas and intestine. [7][8][9] In humans, the Reg gene family currently consists in four well-established members (Reg1a, Reg1b, Reg3a and Reg4), which are found encoded in tandem on chromosome 2p12, except for Reg4, which is found on 1p12. 10 All Regs are produced in the pancreas and small intestine, whereas Reg4 is only constitutively expressed in colonic epithelium, 11 and their expression is enhanced during inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…14 Higher levels of Reg3a were documented in patients with IBD in comparison to healthy controls, while no significant increase was seen in patients with infectious colitis. 8,17 Reg3a is also increased in the plasma of patients with gastrointestinal GVHD, and this protein has been proposed as a useful biomarker that may improve risk stratification of GVHD patients when combined with clinical stage and histological grading. 19 Our study was performed to evaluate whether serum Reg3a concentration is increased in patients with mucosal enteropathies.…”
mentioning
confidence: 99%